2018
DOI: 10.1080/0020739x.2018.1443222
|View full text |Cite
|
Sign up to set email alerts
|

Learning study – promoting and hindering factors in mathematics teaching

Abstract: This article focuses on presenting success factors for a group of teachers in carrying out a learning study in mathematics at their school. The research questions are: what are the actions of the school teaching community during development projects? What factors enable a group of teachers to carry out a learning study at their school? Activity theory provides a holistic framework to investigate relationships among the components present in a learning study. The results are based on analysis of interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Earlier research indicates that struggling learners gain more than do other learners when a learning study approach is used (Kwok and Chik, 2005;Fung-Lo and Marton, 2005;Olteanu, 2018). This study complements previous knowledge by offering a more nuanced understanding, as we have investigated individual learners' achievement in depth.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Earlier research indicates that struggling learners gain more than do other learners when a learning study approach is used (Kwok and Chik, 2005;Fung-Lo and Marton, 2005;Olteanu, 2018). This study complements previous knowledge by offering a more nuanced understanding, as we have investigated individual learners' achievement in depth.…”
Section: Discussionmentioning
confidence: 75%
“…Some of these studies show that learning studies may help low-achieving students' learning. Olteanu (2018), for instance, showed that all students' learning improved, but that students who "have struggled with mathematics and who have the greatest need for explanations" (p. 983) made the greatest progress. In a research project targeting students' individual differences, learning studies in mathematics and other school subjects were conducted (Fung-Lo and Marton, 2005).…”
Section: Students In Need Of Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Efter att ha studerat elevers lärande genom identiska test före och efter learning study-lektionen, observerade forskarna att den största ökningen av lärande återfanns bland elever med lägst resultat på förtestet (Lo & Marton, 2005). I liknande resultat hävdas att kollegialt arbete i form av learning study har visat sig vara särskilt fördelaktigt för elever som kämpar med matematik (Kwok & Chik, 2005;Olteanu, 2018). Mer preciserat framkom att alla elevers lärande förbättrades, men att elever som "har kämpat med matematik och som har störst behov av förklaringar" (Olteanu, 2018, s. 983) gjorde störst framsteg.…”
Section: Förutsättningar För Undervisning Och Lärandeunclassified
“…Detta är i linje med forskning som visar att undervisning enligt learning study-modellen kan vara positiv för elevers lärande (Ex. Lo et al, 2005;Lo & Marton, 2005;Ming Cheung & Wong, 2014;Olteanu, 2018). Trots detta saknades analyser av huruvida undervisningens utformning lyckades bidra till lärande på en individuell nivå i licentiatuppsatsen samt artikel 1 och 2 (Lövström, 2015;Runesson Kempe & Lövström, 2017;Runesson et al, 2018).…”
Section: Interdisciplinärt Angreppssätt För Lärande På Kollektiv Och ...unclassified